2019
DOI: 10.1111/asej.12190
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Dynamic Relationships between Physical Infrastructure, Financial Development and Economic Growth in India

Abstract: This paper investigates the dynamic relationships between physical infrastructure, financial development and economic growth in the case of India, using the autoregressive distributed lag and the Toda-Yamamoto causality approach for the period 1980 to 2016. A physical infrastructure index and a financial development index are constructed using the principal component analysis. The empirical results suggest that physical infrastructure has a positive effect on economic growth both in the long run and short run,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 37 publications
3
13
0
2
Order By: Relevance
“…In other words, higher economic growth is driven by the development of infrastructure areas while greater development in infrastructure areas has also resulted significant economic growth in India. This finding is consistent with Pradhan et al (2013) and Mohanty and Bhanumurthy (2018) who found the presence of bi-directional causality between economic growth and physical infrastructure in Indian context and also with the study by Chi and Baek (2016) showing feedback relationship between transport infrastructure and economic output in the U.S. economy. On the other hand, this finding contrasts with Sahoo and Dash (2009) who found only a unidirectional causation from infrastructure development to output growth in case of India and Sahoo et al (2012) in the context of China, and Tong, Yu and Roberts (2014) who found a unidirectional causation from economic growth to transport infrastructure in the U.…”
Section: Analysis Of Long-run Estimatessupporting
confidence: 91%
See 2 more Smart Citations
“…In other words, higher economic growth is driven by the development of infrastructure areas while greater development in infrastructure areas has also resulted significant economic growth in India. This finding is consistent with Pradhan et al (2013) and Mohanty and Bhanumurthy (2018) who found the presence of bi-directional causality between economic growth and physical infrastructure in Indian context and also with the study by Chi and Baek (2016) showing feedback relationship between transport infrastructure and economic output in the U.S. economy. On the other hand, this finding contrasts with Sahoo and Dash (2009) who found only a unidirectional causation from infrastructure development to output growth in case of India and Sahoo et al (2012) in the context of China, and Tong, Yu and Roberts (2014) who found a unidirectional causation from economic growth to transport infrastructure in the U.…”
Section: Analysis Of Long-run Estimatessupporting
confidence: 91%
“…Where, INFI denotes infrastructure development index, TOI is trade openness index and IFA denotes inflation rate which drifts at a high level during most part of the study period affecting the economic productivity in India. Following Barro (2013) and Mohanty and Bhanumurthy (2018), inflation rate is included in the empirical model. Taking the natural logs of both sides of Equation (2) results the following estimable function (Equation 3): …”
Section: Model Specificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Sahoo and Ranjan Kumar (2009) studied the impact of physical infrastructure on growth in the context of India. Along with physical infrastructure, Mohanty and Bhanumurthy (2018) considered financial development while analysing their influence on economic growth. In the context of Bangladesh, Sharif (2013) and Rahman (2007) separately probed into the effect of human capital and financial development, respectively, on growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the last part of this section, different alternative approaches signifying infrastructure for development of economy have been mentioned. The focus of Mohanty and Bhanumurthy (2018) was on the development and maintenance of infrastructure and its influence on the development of economy and government quality. The findings revealed that infrastructure benefits are greater than its costs.…”
Section: Real Gdp Total Factor Productivity (Tfp) and Alternative Approachesmentioning
confidence: 99%